Antibacterial oxygen-barrier PVDC composite film and preparation method thereof

By adding antibacterial microcapsules and thermal conductivity enhancers to the PVDC composite membrane, the problems of poor antibacterial properties and poor thermal instability of the existing PVDC composite membrane are solved, and higher antibacterial properties, heat resistance and oxidation resistance are achieved, while improving thermal stability and mechanical properties.

CN119552583APending Publication Date: 2025-03-04安尔鲜生物科技(常州)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411748299.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing PVDC composite films have poor antibacterial properties and poor thermal instability under high temperature conditions, resulting in the formation of polyacetylene and affecting the color and quality of the products.

Method used

An antibacterial oxygen-hindered PVDC composite film including a PE film layer, an EVA hot melt adhesive film layer and a PVDC film layer is used, and the PVDC film layer is coated with PVDC emulsion, and antibacterial microcapsules and thermal reinforcement are added to the PVDC emulsion.

Benefits of technology

It significantly improves the antibacterial, heat resistance and oxidation resistance of the composite film, improves the thermal stability and mechanical properties, and avoids the formation of polyacetylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164320570000161
    Figure BDA0005164320570000161
  • Figure BDA0005164320570000171
    Figure BDA0005164320570000171
Patent Text Reader

Abstract

The invention discloses an antibacterial oxygen-resistant PVDC composite film and a preparation method thereof, and relates to the field of composite films, the antibacterial oxygen-resistant PVDC composite film comprises a PE film layer, an EVA hot melt adhesive film layer and a PVDC film layer from inside to outside; the PVDC thin film layer is obtained by coating a PVDC emulsion; the PVDC emulsion is prepared from vinylidene chloride, vinyl chloride, methyl acrylate, an emulsifier, an initiator, a pH buffer agent, deionized water, antibacterial microcapsules and a heat-conducting enhancer. PVDC has excellent oxygen barrier performance, and the requirement of the PVDC composite film on the oxygen barrier performance is met. The antibacterial microcapsule is obtained by coating origanum vulgare essential oil with cyclodextrin containing a polysiloxane chain and hindered phenol, and the heat conduction enhancer is obtained by introducing an epoxy group to the surface of a carbon nanotube. And the synthesized antibacterial microcapsules and the heat-conducting enhancer are added, so that the antibacterial property, heat resistance, oxidation resistance and mechanical properties of the PVDC composite film are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite films, and in particular to an antibacterial and oxygen-barrier PVDC composite film and a preparation method thereof. Background Art

[0002] Polyvinylidene chloride (PVDC) is a copolymer mainly formed by the polymerization of vinylidene chloride as a monomer. It is an ideal environmentally friendly packaging material with high barrier properties, excellent chemical stability and excellent heat sealing properties. The chlorine atoms in the PVDC molecule are hydrophobic and will not form hydrogen bonds. Oxygen molecules and water molecules find it difficult to move in the PVDC molecule, which makes it have excellent oxygen and moisture barriers. However, PVDC has poor thermal stability and releases toxic hydrogen chloride gas once it encounters high temperatures. Moreover, during the processing and production process, the thermal instability of PVDC at the melt processing temperature will also lead to the formation of polyvinyl chloride, which in turn affects the color and quality of the product and increases the difficulty of production. The PVDC films actually used are mostly films with excellent barrier properties formed by coating copolymer emulsions of vinylidene chloride, vinyl chloride or methyl acrylate. In the prior art, PVDC films are bonded to PVA films, PE films, etc. using adhesives such as EVA hot melt adhesives to form PVDC composite films to meet the use requirements of the mechanical properties and barrier properties of the composite films with synergistic protective effects.

[0003] The antibacterial properties of PVDC composite films in existing technologies are poor. Previous studies have used natural, environmentally friendly, and human-friendly antibacterial agents such as oregano essential oil and chitosan to improve the antibacterial properties of food packaging materials. However, oregano essential oil itself is highly volatile and its activity is accelerated when affected by high temperatures. In addition, oregano essential oil is an aromatic phenol that is easily oxidized, so its use in PVDC composite films is limited. Summary of the Invention

[0004] In order to solve the above technical problems, the present invention provides an antibacterial and oxygen-barrier PVDC composite film and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An antibacterial and oxygen-barrier PVDC composite film comprises, from the inside out, a PE film layer, an EVA hot-melt adhesive film layer, and a PVDC film layer; the PE film layer is composed of a PE film; the EVA hot-melt adhesive film layer is prepared using an EVA composite adhesive; and the PVDC film layer is obtained by coating with a PVDC emulsion;

[0007] The PVDC emulsion comprises the following raw materials in parts by weight: 100 parts of vinylidene chloride, 10-15 parts of vinyl chloride, 60-70 parts of methyl acrylate, 5-7 parts of emulsifier, 2-4 parts of initiator, 0.5-1.5 parts of pH buffer, 80-100 parts of deionized water, 5-10 parts of antibacterial microcapsules, and 10-20 parts of thermal conductivity enhancer;

[0008] The emulsifier is prepared by mixing sodium lauryl sulfate and dodecylphenol polyoxyethylene ether in a mass ratio of 2.5:1, the initiator is potassium persulfate, and the pH buffer is disodium hydrogen phosphate;

[0009] The preparation of the antibacterial and oxygen-barrier PVDC composite film comprises the following steps:

[0010] Step S1: adding vinylidene chloride, vinyl chloride, methyl acrylate, emulsifier, pH buffer and deionized water to a high-pressure reactor, stirring at room temperature and a speed of 200 r / min for 15-25 minutes to obtain a pre-emulsion, then adding an initiator to the deionized water, stirring for 5 minutes, adding the pre-emulsion to the high-pressure reactor, venting, starting stirring, adjusting the speed to 300 r / min, raising the temperature to 55-65° C., stirring and reacting for 5 hours, heating to 65-75° C. and maturing for 1 hour, starting to cool to room temperature after 15 minutes, then adding antibacterial microcapsules and thermal conductivity enhancer, continuing stirring for 30 minutes, and discharging to obtain a PVDC emulsion; the amount ratio of the deionized water used in the two times is 4:1;

[0011] Step S2: placing a PE film to form a PE film layer, then coating the PE film with EVA composite glue to a thickness of 5 μm to form an EVA hot melt adhesive film layer, and finally coating the PVDC emulsion on the EVA hot melt adhesive film layer to a thickness of 15-18 μm, and then drying at 100-110°C for 25-35 minutes to form a PVDC film layer, thereby obtaining an antibacterial and oxygen-barrier PVDC composite film.

[0012] The preparation of the antibacterial microcapsules comprises the following steps:

[0013] Step A1: Vinyl polydimethylsiloxane was added to dichloromethane with stirring, followed by the addition of 3-chloroperoxybenzoic acid. The mixture was stirred at room temperature for 4-5 hours to obtain the epoxy product. Ethylenediamine cyclodextrin (for the preparation process, refer to the synthesis process of CDen (ethylenediamine cyclodextrin) in Section 2.2.1 of the paper "Synthesis of Degradable Amphiphilic Polyesters Containing Amino-Modified Beta-Cyclodextrin and Their Controlled Release of Proteins and Anticancer Drugs") and the epoxy product were added to a round-bottom flask. Dimethyl sulfoxide was then added, and the mixture was stirred at 50°C for 24 hours. The mixture was filtered and dried to obtain the cyclodextrin product.

[0014] Furthermore, the usage ratio of vinyl polydimethylsiloxane, dichloromethane and 3-chloroperoxybenzoic acid is 10-12 g: 55-65 mL: 18-20 g; the usage ratio of ethylenediamine cyclodextrin, epoxy product and dimethyl sulfoxide is 12-12.5 g: 5-6 g: 35-40 mL;

[0015] During the reaction process of step A1, the carbon-carbon double bond in the vinyl polydimethylsiloxane is oxidized to an epoxy group to obtain an epoxy product; the amino group of the ethylenediamine cyclodextrin reacts with the epoxy group of the epoxy product to generate a cyclodextrin product containing an alcoholic hydroxyl group and a polysiloxane chain;

[0016] Step A2: 3,5-di-tert-butyl-4-hydroxyphenylacetic acid is added to DMF, and dichlorothionyl is added with stirring. The mixture is refluxed and stirred at 50°C for 4-5 hours to obtain an acyl chloride product. The cyclodextrin product, pyridine, triethylamine, and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1. The acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2. The mixed solution 2 is slowly added dropwise to the mixed solution 1 in a 0°C ice-water bath. After the addition is complete, the temperature is raised to 40°C, and the mixture is stirred at this constant temperature for 8-10 hours. The temperature is then raised to 100-110°C, stirring is continued for 1-2 hours, and the mixture is distilled under reduced pressure to obtain an esterification product.

[0017] Furthermore, the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, DMF, and thionyl chloride is 0.1 mol: 55-65 mL: 0.12-0.15 mol; the usage ratio of cyclodextrin product, pyridine, triethylamine, and dimethyl sulfoxide is 14-16 g: 10-15 mL: 15-20 mL: 35-45 mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 0.1 mol: 65-75 mL; the usage ratio of mixed solution 1 and mixed solution 2 is 90-100 mL: 85-95 mL;

[0018] During the reaction of step A2, the carboxyl group of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid reacts with thionyl chloride to form an acyl chloride product; the acyl chloride product reacts with the alcoholic hydroxyl group of the cyclodextrin product to form an esterification product containing hindered phenol, polysiloxane chain and cyclodextrin;

[0019] Step A3: adding the esterified product to distilled water and stirring for 30 minutes to obtain solution a, then adding oregano essential oil to anhydrous ethanol to obtain solution b, slowly adding solution b to solution a while stirring, stirring at 50°C for 3 hours, then placing in a refrigerator at 4°C overnight, extracting with ethyl acetate and freeze-drying for 24 hours to obtain antibacterial microcapsules;

[0020] Furthermore, the usage ratio of the esterification product and distilled water is 1 g:10 mL; the usage ratio of oregano essential oil and anhydrous ethanol is 1 mL:1 mL; the usage ratio of solution b and solution a is 2.5-3 mL:12-13 mL;

[0021] During the reaction of step A3, antibacterial microcapsules were prepared by a saturated aqueous solution method using oregano essential oil as the core material and cyclodextrin containing hindered phenol and polysiloxane chains as the wall material.

[0022] The preparation of the thermal conductivity enhancer comprises the following steps:

[0023] Step B1: After ball milling the carbon nanotubes for 2-3 hours, the carbon nanotubes were added to the mixed acid, stirred, and refluxed at 100-120°C for 1.5-2.5 hours. After dilution, filtration, and washing, the mixture was dried in an oven at 110°C for 6-8 hours to obtain carboxyl-modified carbon nanotubes. The carboxyl-modified carbon nanotubes were added to DMF, and dichloride was added with stirring. The mixture was refluxed and stirred at 50°C for 4-5 hours to obtain the acyl chloride product 1.

[0024] Furthermore, the carbon nanotubes and the mixed acid are used in a ratio of 10-15 g to 80-90 mL, wherein the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of the concentrated sulfuric acid and concentrated nitric acid are both 98%; the carboxyl-modified carbon nanotubes, DMF, and thionyl chloride are used in a ratio of 1.5-2.0 g to 30-40 mL to 0.12-0.15 mol;

[0025] During the reaction of step B1, after mixed acid treatment, carbon nanotubes with open ends and modified with carboxyl groups are obtained, and the carboxyl groups of the carboxyl-modified carbon nanotubes react with thionyl chloride to form an acyl chloride product 1;

[0026] Step B2: p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide are added to a flask to obtain a mixture a; the acyl chloride product 1 is added to dimethyl sulfoxide to obtain a mixture b, and the mixture b is slowly added dropwise to the mixture a in a 0°C ice-water bath. After the addition is complete, the temperature is raised to 40°C and stirred at this constant temperature for 8-10 hours, and then the temperature is raised to 100-110°C, stirring is continued for 1-2 hours, and the mixture is distilled under reduced pressure to obtain the nitro product;

[0027] Furthermore, the usage ratio of p-nitrobenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.01-0.015 mol: 0.1 mol: 35-45 mL; the usage ratio of acyl chloride product 1 and dimethyl sulfoxide is 5-6 g: 30-40 mL; the usage ratio of mixed solution a and mixed solution b is 50-60 mL: 90-100 mL;

[0028] During the reaction of step B2, the acyl chloride product 1 reacts with the alcoholic hydroxyl group of p-nitrobenzyl alcohol to generate a nitro product containing carbon nanotubes;

[0029] Step B3: Add the nitro product and ethyl acetate to a three-necked flask, raise the temperature to 45-55°C, start reflux stirring, then add sodium dithionite, and continue to reflux and stir for 1-1.5 hours to obtain an aromatic primary amine; add epichlorohydrin, toluene, an aromatic primary amine, and tetrabutylammonium bromide to the flask, start stirring, and condense and reflux at 110°C for 3 hours to obtain a ring-opened product, add the ring-opened product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract, and distill to obtain a thermal conductivity enhancer;

[0030] Furthermore, the usage ratio of the nitro product, ethyl acetate, and sodium dithionite is 16-18 g:110-120 mL:35-40 g; the usage ratio of epichlorohydrin, aromatic primary amine, toluene, and tetrabutylammonium bromide is 27-30 g:20-25 g:120-130 mL:0.05-0.08 mol; the usage ratio of the ring-opening product and sodium hydroxide solution is 3-4 g:10 mL, and the mass fraction of the sodium hydroxide solution is 10%;

[0031] During the reaction of step B3, the nitro group in the nitro product is reduced to an amino group to obtain an aromatic primary amine; under the catalytic action of tetrabutylammonium bromide, the amino group of the aromatic primary amine first reacts with the epoxy group of epichlorohydrin to obtain a ring-opened product, and then the hydroxyl group and chlorine atom of the ring-opened product are closed in a sodium hydroxide solution to generate an epoxy-containing thermal conductivity enhancer.

[0032] The present invention provides an antibacterial and oxygen-barrier PVDC composite film comprising, from the inside out, a PE film layer, an EVA hot-melt adhesive layer, and a PVDC film layer. The PVDC film layer is coated with a PVDC emulsion containing the following raw materials: vinylidene chloride, vinyl chloride, methyl acrylate, an emulsifier, an initiator, a pH buffer, deionized water, antibacterial microcapsules, and a thermal conductivity enhancer. The PVDC material exhibits excellent oxygen barrier properties, meeting the requirements for oxygen barrier properties of the antibacterial and oxygen-barrier PVDC composite film.

[0033] The synthesized antibacterial microcapsules are prepared by a saturated aqueous solution method using cyclodextrin introduced with polysiloxane chains and hindered phenol as the wall material and oregano essential oil as the core material. Oregano essential oil is a yellow-red or brown-red essential oil extracted and purified from the roots, stems and leaves of the oregano plant. Its main components are carvacrol and thymol, and it has the advantages of broad-spectrum bactericidal, biodegradable, safe and non-toxic. After being microencapsulated, it is used in PVDC composite films. It is not easy to volatilize and can be slowly released to exert antibacterial effects, so its stability is improved, which is convenient for production and application. When the composite film is in a high-temperature environment, the polysiloxane chains are not easy to break due to the high Si-O-Si bonds and Si-C bonds contained therein, so that the heat resistance of the antibacterial microcapsules is improved, and the cyclodextrin will not be destroyed due to the temperature increase, which will cause the oregano essential oil to volatilize rapidly, thereby avoiding the reduction of the antibacterial property of the composite film. The hindered phenol structure can terminate the oxidative degradation reaction chain and has a good antioxidant effect. Introducing it into the wall material of the antibacterial microcapsules can protect the oregano essential oil from oxidation and improve the antioxidant property of the PVDC film. Therefore, adding the antibacterial microcapsules significantly improves the heat resistance, antioxidant property and antibacterial property of the PVDC composite film.

[0034] The synthesized thermal conductivity enhancer is obtained by modifying carbon nanotubes and introducing epoxy groups onto their surfaces. Organic modification of the carbon nanotubes increases their compatibility with the matrix, allowing for more uniform dispersion in the PVDC emulsion, improving the mechanical properties of the composite film. Furthermore, the carbon nanotubes possess excellent thermal conductivity, dispersing heat from the composite film's surface and preventing accumulated heat from adversely affecting its performance. The epoxy groups absorb hydrogen chloride produced during the thermal decomposition of vinylidene chloride and vinyl chloride copolymers, preventing further thermal degradation and enhancing the thermal stability of the PVDC emulsion, thereby improving the thermal stability and processing performance of the PVDC film. Therefore, the addition of the thermal conductivity enhancer improves the thermal stability and mechanical properties of the composite film. DETAILED DESCRIPTION

[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0036] Example 1

[0037] An antibacterial microcapsule, the preparation of which comprises the following steps:

[0038] Step A1: Add vinyl polydimethylsiloxane to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4 hours to obtain the epoxy product; add ethylenediamine cyclodextrin and the epoxy product to a round-bottom flask, then add dimethyl sulfoxide, stir at 50°C for 24 hours, filter, and dry to obtain the cyclodextrin product; the amount ratio of vinyl polydimethylsiloxane, dichloromethane, and 3-chloroperoxybenzoic acid is 10g:55mL:18g; the amount ratio of ethylenediamine cyclodextrin, epoxy product, and dimethyl sulfoxide is 12g:5g:35mL;

[0039] Step A2: 3,5-di-tert-butyl-4-hydroxyphenylacetic acid was added to DMF, and dichlorothionyl was added under stirring. The mixture was refluxed and stirred at 50°C for 4 hours to obtain an acyl chloride product. The cyclodextrin product, pyridine, triethylamine and dimethyl sulfoxide were added to a flask to obtain a mixture 1. The acyl chloride product was added to dimethyl sulfoxide to obtain a mixture 2. The mixture 2 was slowly added dropwise to the mixture 1 in a 0°C ice-water bath. After the addition was complete, the temperature was raised to 40°C, and the mixture was stirred at a constant temperature for 8 hours, and then the temperature was raised to 10 0℃, continue stirring for 1h, and distill under reduced pressure to obtain the esterification product; the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, DMF, and dithionyl chloride is 0.1mol:55mL:0.12mol; the usage ratio of cyclodextrin product, pyridine, triethylamine, and dimethyl sulfoxide is 14g:10mL:15mL:35mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 0.1mol:65mL; ​​the usage ratio of mixed solution 1 and mixed solution 2 is 90mL:85mL;

[0040] Step A3: The esterification product is added to distilled water and stirred for 30 minutes to obtain solution a. The oregano essential oil is then added to anhydrous ethanol to obtain solution b. Solution b is slowly added to solution a while stirring, and the mixture is stirred at 50°C for 3 hours. The mixture is then placed in a refrigerator at 4°C overnight, extracted with ethyl acetate, and freeze-dried for 24 hours to obtain antibacterial microcapsules. The amount ratio of the esterification product to distilled water is 1 g:10 mL; the amount ratio of the oregano essential oil to anhydrous ethanol is 1 mL:1 mL; and the amount ratio of solution b to solution a is 2.5 mL:12 mL.

[0041] Example 2

[0042] An antibacterial microcapsule, the preparation of which comprises the following steps:

[0043] Step A1: Add vinyl polydimethylsiloxane to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4.5 hours to obtain the epoxy product; add ethylenediamine cyclodextrin and the epoxy product to a round-bottom flask, then add dimethyl sulfoxide, stir at 50°C for 24 hours, filter, and dry to obtain the cyclodextrin product; the amount ratio of vinyl polydimethylsiloxane, dichloromethane, and 3-chloroperoxybenzoic acid is 11g:60mL:19g; the amount ratio of ethylenediamine cyclodextrin, epoxy product, and dimethyl sulfoxide is 12.3g:5.5g:37mL;

[0044] Step A2: 3,5-di-tert-butyl-4-hydroxyphenylacetic acid was added to DMF, and dichlorothionyl was added under stirring. The mixture was refluxed and stirred at 50°C for 4.5 hours to obtain an acyl chloride product. The cyclodextrin product, pyridine, triethylamine and dimethyl sulfoxide were added to a flask to obtain a mixture 1. The acyl chloride product was added to dimethyl sulfoxide to obtain a mixture 2. The mixture 2 was slowly added dropwise to the mixture 1 in a 0°C ice-water bath. After the addition was complete, the temperature was raised to 40°C, and the mixture was stirred at a constant temperature for 9 hours, and then the temperature was raised to 10 0℃, continue stirring for 1.5h, and distill under reduced pressure to obtain the esterification product; the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, DMF, and dithionyl chloride is 0.1mol:60mL:0.13mol; the usage ratio of cyclodextrin product, pyridine, triethylamine, and dimethyl sulfoxide is 15g:13mL:18mL:40mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 0.1mol:70mL; the usage ratio of mixed solution 1 and mixed solution 2 is 95mL:90mL;

[0045] Step A3: The esterification product is added to distilled water and stirred for 30 minutes to obtain solution a. The oregano essential oil is then added to anhydrous ethanol to obtain solution b. Solution b is slowly added to solution a while stirring, and the mixture is stirred at 50°C for 3 hours. The mixture is then placed in a refrigerator at 4°C overnight, extracted with ethyl acetate, and freeze-dried for 24 hours to obtain antibacterial microcapsules. The amount ratio of the esterification product to distilled water is 1 g:10 mL; the amount ratio of the oregano essential oil to anhydrous ethanol is 1 mL:1 mL; and the amount ratio of solution b to solution a is 2.8 mL:12.5 mL.

[0046] Example 3

[0047] An antibacterial microcapsule, the preparation of which comprises the following steps:

[0048] Step A1: Add vinyl polydimethylsiloxane to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 5 hours to obtain the epoxy product; add ethylenediamine cyclodextrin and the epoxy product to a round-bottom flask, then add dimethyl sulfoxide, stir at 50°C for 24 hours, filter, and dry to obtain the cyclodextrin product; the amount ratio of vinyl polydimethylsiloxane, dichloromethane, and 3-chloroperoxybenzoic acid is 12g:65mL:20g; the amount ratio of ethylenediamine cyclodextrin, epoxy product, and dimethyl sulfoxide is 12.5g:6g:40mL;

[0049] Step A2: 3,5-di-tert-butyl-4-hydroxyphenylacetic acid was added to DMF, and dichlorothionyl was added under stirring. The mixture was refluxed and stirred at 50°C for 5 hours to obtain an acyl chloride product. The cyclodextrin product, pyridine, triethylamine and dimethyl sulfoxide were added to a flask to obtain a mixed solution 1. The acyl chloride product was added to dimethyl sulfoxide to obtain a mixed solution 2. The mixed solution 2 was slowly added dropwise to the mixed solution 1 in a 0°C ice-water bath. After the addition was completed, the temperature was raised to 40°C, and the mixture was stirred at a constant temperature for 10 hours, and then the temperature was raised to 11 0℃, continue stirring for 2h, and distill under reduced pressure to obtain the esterification product; the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, DMF, and thionyl chloride is 0.1mol:65mL:0.15mol; the usage ratio of cyclodextrin product, pyridine, triethylamine, and dimethyl sulfoxide is 16g:15mL:20mL:45mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 0.1mol:75mL; the usage ratio of mixed solution 1 and mixed solution 2 is 100mL:95mL;

[0050] Step A3: The esterification product is added to distilled water and stirred for 30 minutes to obtain solution a. The oregano essential oil is then added to anhydrous ethanol to obtain solution b. Solution b is slowly added to solution a while stirring, and the mixture is stirred at 50°C for 3 hours. The mixture is then placed in a refrigerator at 4°C overnight, extracted with ethyl acetate, and freeze-dried for 24 hours to obtain antibacterial microcapsules. The amount ratio of the esterification product to distilled water is 1 g:10 mL; the amount ratio of the oregano essential oil to anhydrous ethanol is 1 mL:1 mL; and the amount ratio of solution b to solution a is 3 mL:13 mL.

[0051] Example 4

[0052] A thermal conductivity enhancer, the preparation of which comprises the following steps:

[0053] Step B1: After ball milling the carbon nanotubes for 2 hours, the carbon nanotubes were added to the mixed acid, stirred, and refluxed at 100°C for 1.5 hours. After dilution, filtration, and washing, the mixture was dried in an oven at 110°C for 6 hours to obtain carboxyl-modified carbon nanotubes; the carboxyl-modified carbon nanotubes were added to DMF, thionyl chloride was added under stirring, and the mixture was refluxed and stirred at 50°C for 4 hours to obtain the acyl chloride product 1; the amount ratio of the carbon nanotubes to the mixed acid was 10 g:80 mL, and the mixed acid was prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of the concentrated sulfuric acid and concentrated nitric acid were both 98%; the amount ratio of the carboxyl-modified carbon nanotubes, DMF, and thionyl chloride was 1.5 g:30 mL:0.12 mol;

[0054] Step B2: p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide were added to a flask to obtain a mixed solution a; the acyl chloride product 1 was added to dimethyl sulfoxide to obtain a mixed solution b; the mixed solution b was slowly added dropwise to the mixed solution a in a 0°C ice-water bath; after the addition was complete, the temperature was raised to 40°C, and the mixture was stirred at this constant temperature for 8 hours, and then the temperature was raised to 100°C, and the stirring was continued for 1 hour, and the nitro product was obtained by distillation under reduced pressure; the amount ratio of p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide was 0.1 mol: 0.01 mol: 0.1 mol: 35 mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide was 5 g: 30 mL; the amount ratio of the mixed solution a to the mixed solution b was 50 mL: 90 mL;

[0055] Step B3: Add the nitro product and ethyl acetate to a three-necked flask, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux and stir for 1 hour to obtain an aromatic primary amine; add epichlorohydrin, toluene, an aromatic primary amine and tetrabutylammonium bromide to the flask, start stirring, and condense and reflux at 110°C for 3 hours to obtain a ring-opening product, add the ring-opening product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain a thermal conductivity enhancer; the amount ratio of the nitro product, ethyl acetate, and sodium dithionite is 16g:110mL:35g; the amount ratio of epichlorohydrin, aromatic primary amine, toluene and tetrabutylammonium bromide is 27g:20g:120mL:0.05mol; the amount ratio of the ring-opening product and sodium hydroxide solution is 3g:10mL, and the mass fraction of the sodium hydroxide solution is 10%.

[0056] Example 5

[0057] A thermal conductivity enhancer, the preparation of which comprises the following steps:

[0058] Step B1: After ball milling the carbon nanotubes for 2.5 hours, the carbon nanotubes were added to the mixed acid, stirred, and refluxed at 110°C for 2.0 hours. After dilution, filtration, and washing, the carbon nanotubes were dried in an oven at 110°C for 7 hours to obtain carboxyl-modified carbon nanotubes. The carboxyl-modified carbon nanotubes were added to DMF, and dithionyl chloride was added under stirring. The mixture was refluxed and stirred at 50°C for 4.5 hours to obtain the acyl chloride product 1. The amount ratio of the carbon nanotubes to the mixed acid was 13 g:85 mL. The mixed acid was prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of the concentrated sulfuric acid and concentrated nitric acid were both 98%. The amount ratio of the carboxyl-modified carbon nanotubes, DMF, and dithionyl chloride was 1.8 g:35 mL:0.13 mol.

[0059] Step B2: p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide were added to a flask to obtain a mixed solution a; the acyl chloride product 1 was added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b was slowly added dropwise to the mixed solution a in a 0°C ice-water bath. After the addition was complete, the temperature was raised to 40°C and stirred at this constant temperature for 9 hours, and then the temperature was raised to 105°C, and stirring was continued for 1.5 hours. The nitro product was obtained by distillation under reduced pressure; the amount ratio of p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide was 0.1 mol:0.013 mol:0.1 mol:40 mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide was 5.5 g:35 mL; the amount ratio of the mixed solution a to the mixed solution b was 55 mL:95 mL;

[0060] Step B3: Add the nitro product and ethyl acetate to a three-necked flask, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux and stir for 1.3 hours to obtain an aromatic primary amine; add epichlorohydrin, toluene, an aromatic primary amine and tetrabutylammonium bromide to the flask, start stirring, and condense and reflux at 110°C for 3 hours to obtain a ring-opening product, add the ring-opening product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain a thermal conductivity enhancer; the amount ratio of the nitro product, ethyl acetate, and sodium dithionite is 17g:115mL:37g; the amount ratio of epichlorohydrin, aromatic primary amine, toluene and tetrabutylammonium bromide is 28g:23g:125mL:0.06mol; the amount ratio of the ring-opening product and sodium hydroxide solution is 3.5g:10mL, and the mass fraction of the sodium hydroxide solution is 10%.

[0061] Example 6

[0062] A thermal conductivity enhancer, the preparation of which comprises the following steps:

[0063] Step B1: After ball milling the carbon nanotubes for 3 hours, the mixture was added to the mixed acid, stirred, and refluxed at 120°C for 2.5 hours. After dilution, filtration, and washing, the mixture was dried in an oven at 110°C for 8 hours to obtain carboxyl-modified carbon nanotubes; the carboxyl-modified carbon nanotubes were added to DMF, thionyl chloride was added under stirring, and the mixture was refluxed and stirred at 50°C for 5 hours to obtain the acyl chloride product 1; the amount ratio of the carbon nanotubes to the mixed acid was 15g:90mL, and the mixed acid was prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of the concentrated sulfuric acid and concentrated nitric acid were both 98%; the amount ratio of the carboxyl-modified carbon nanotubes, DMF, and thionyl chloride was 2.0g:40mL:0.15mol;

[0064] Step B2: p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide were added to a flask to obtain a mixed solution a; the acyl chloride product 1 was added to dimethyl sulfoxide to obtain a mixed solution b; the mixed solution b was slowly added dropwise to the mixed solution a in a 0°C ice-water bath; after the addition was complete, the temperature was raised to 40°C, and the reaction was stirred at a constant temperature for 10 hours, and then the temperature was raised to 110°C, and stirring was continued for 2 hours, and the nitro product was obtained by distillation under reduced pressure; the amount ratio of p-nitrobenzyl alcohol, pyridine, triethylamine, and dimethyl sulfoxide was 0.1 mol:0.015 mol:0.1 mol:45 mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide was 6 g:40 mL; the amount ratio of the mixed solution a to the mixed solution b was 60 mL:100 mL;

[0065] Step B3: Add the nitro product and ethyl acetate to a three-necked flask, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux and stir for 1.5 hours to obtain an aromatic primary amine; add epichlorohydrin, toluene, an aromatic primary amine and tetrabutylammonium bromide to the flask, start stirring, and condense and reflux at 110°C for 3 hours to obtain a ring-opening product, add the ring-opening product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain a thermal conductivity enhancer; the amount ratio of the nitro product, ethyl acetate, and sodium dithionite is 18g:120mL:40g; the amount ratio of epichlorohydrin, aromatic primary amine, toluene and tetrabutylammonium bromide is 30g:25g:130mL:0.08mol; the amount ratio of the ring-opening product and sodium hydroxide solution is 4g:10mL, and the mass fraction of the sodium hydroxide solution is 10%.

[0066] Example 7

[0067] An antibacterial and oxygen-barrier PVDC composite film, comprising, from the inside out, a PE film layer, an EVA hot-melt adhesive film layer, and a PVDC film layer; the PE film layer is composed of a PE film; the EVA hot-melt adhesive film layer is prepared using an EVA composite adhesive; the PVDC film layer is coated with a PVDC emulsion; the PVDC emulsion comprises the following raw materials in parts by weight: 100 parts of vinylidene chloride, 10 parts of vinyl chloride, 60 parts of methyl acrylate, 5 parts of an emulsifier, 2 parts of an initiator, 0.5 parts of a pH buffer, 80 parts of deionized water, 5 parts of antibacterial microcapsules, and 10 parts of a thermal conductivity enhancer; the emulsifier is a mixture of sodium lauryl sulfate and dodecylphenol polyoxyethylene ether in a mass ratio of 2.5:1; the initiator is potassium persulfate; and the pH buffer is disodium hydrogen phosphate;

[0068] The preparation of the antibacterial and oxygen-barrier PVDC composite film comprises the following steps:

[0069] Step S1: adding vinylidene chloride, vinyl chloride, methyl acrylate, emulsifier, pH buffer and deionized water to a high-pressure reactor, stirring at room temperature and a speed of 200 r / min for 15 minutes to obtain a pre-emulsion, then adding an initiator to the deionized water, stirring for 5 minutes, adding the mixture to the high-pressure reactor, venting, starting stirring, adjusting the speed to 300 r / min, raising the temperature to 55°C, stirring and reacting for 5 hours, heating to 65°C and maturing for 1 hour, and starting to cool to room temperature after 15 minutes, then adding antibacterial microcapsules and thermal conductivity enhancer, continuing stirring for 30 minutes, and discharging to obtain a PVDC emulsion; the amount ratio of the deionized water used in the two times is 4:1;

[0070] Step S2: placing a PE film to form a PE film layer, then coating the PE film with EVA composite glue to a thickness of 5 μm to form an EVA hot melt adhesive film layer, and finally coating the PVDC emulsion on the EVA hot melt adhesive film layer to a thickness of 15 μm, and then drying at 100° C. for 25 minutes to form a PVDC film layer, thereby obtaining an antibacterial and oxygen-barrier PVDC composite film.

[0071] Example 8

[0072] An antibacterial and oxygen-barrier PVDC composite film, comprising, from the inside out, a PE film layer, an EVA hot-melt adhesive film layer, and a PVDC film layer; the PE film layer is composed of a PE film; the EVA hot-melt adhesive film layer is prepared using an EVA composite adhesive; the PVDC film layer is coated with a PVDC emulsion; the PVDC emulsion comprises the following raw materials in parts by weight: 100 parts of vinylidene chloride, 13 parts of vinyl chloride, 65 parts of methyl acrylate, 6 parts of an emulsifier, 3 parts of an initiator, 1.0 part of a pH buffer, 90 parts of deionized water, 8 parts of antibacterial microcapsules, and 15 parts of a thermal conductivity enhancer; the emulsifier is a mixture of sodium lauryl sulfate and dodecylphenol polyoxyethylene ether in a mass ratio of 2.5:1; the initiator is potassium persulfate; and the pH buffer is disodium hydrogen phosphate;

[0073] The preparation of the antibacterial and oxygen-barrier PVDC composite film comprises the following steps:

[0074] Step S1: adding vinylidene chloride, vinyl chloride, methyl acrylate, emulsifier, pH buffer and deionized water to a high-pressure reactor, stirring at room temperature and a speed of 200 r / min for 25 minutes to obtain a pre-emulsion, then adding an initiator to the deionized water, stirring for 5 minutes, adding the mixture to the high-pressure reactor, venting, starting stirring, adjusting the speed to 300 r / min, raising the temperature to 65°C, stirring and reacting for 5 hours, heating to 75°C and maturing for 1 hour, and starting to cool to room temperature after 15 minutes, then adding antibacterial microcapsules and thermal conductivity enhancer, continuing stirring for 30 minutes, and discharging to obtain a PVDC emulsion; the amount ratio of the deionized water used in the two times is 4:1;

[0075] Step S2: placing a PE film to form a PE film layer, then coating the PE film with EVA composite glue to a thickness of 5 μm to form an EVA hot melt adhesive film layer, and finally coating the PVDC emulsion on the EVA hot melt adhesive film layer to a thickness of 16 μm, and then drying at 105° C. for 30 minutes to form a PVDC film layer, thereby obtaining an antibacterial and oxygen-barrier PVDC composite film.

[0076] Example 9

[0077] An antibacterial and oxygen-barrier PVDC composite film, comprising, from the inside out, a PE film layer, an EVA hot-melt adhesive film layer, and a PVDC film layer; the PE film layer is composed of a PE film; the EVA hot-melt adhesive film layer is prepared using an EVA composite adhesive; the PVDC film layer is coated with a PVDC emulsion; the PVDC emulsion comprises the following raw materials in parts by weight: 100 parts of vinylidene chloride, 15 parts of vinyl chloride, 70 parts of methyl acrylate, 7 parts of an emulsifier, 4 parts of an initiator, 1.5 parts of a pH buffer, 100 parts of deionized water, 10 parts of antibacterial microcapsules, and 20 parts of a thermal conductivity enhancer; the emulsifier is a mixture of sodium lauryl sulfate and dodecylphenol polyoxyethylene ether in a mass ratio of 2.5:1; the initiator is potassium persulfate; and the pH buffer is disodium hydrogen phosphate;

[0078] The preparation of the antibacterial and oxygen-barrier PVDC composite film comprises the following steps:

[0079] Step S1: adding vinylidene chloride, vinyl chloride, methyl acrylate, emulsifier, pH buffer and deionized water to a high-pressure reactor, stirring at room temperature and a speed of 200 r / min for 25 minutes to obtain a pre-emulsion, then adding an initiator to the deionized water, stirring for 5 minutes, adding the mixture to the high-pressure reactor, venting, starting stirring, adjusting the speed to 300 r / min, raising the temperature to 65°C, stirring and reacting for 5 hours, heating to 75°C and maturing for 1 hour, and starting to cool to room temperature after 15 minutes, then adding antibacterial microcapsules and thermal conductivity enhancer, continuing stirring for 30 minutes, and discharging to obtain a PVDC emulsion; the amount ratio of the deionized water used in the two times is 4:1;

[0080] Step S2: placing a PE film to form a PE film layer, then coating the PE film with EVA composite glue to a thickness of 5 μm to form an EVA hot melt adhesive film layer, and finally coating the PVDC emulsion on the EVA hot melt adhesive film layer to a thickness of 18 μm, and then drying at 110° C. for 35 minutes to form a PVDC film layer, thereby obtaining an antibacterial and oxygen-barrier PVDC composite film.

[0081] Comparative Example 1

[0082] This comparative example is obtained by bonding a commercially available PVDC film and a PE film using EVA hot melt adhesive according to step S2 of Example 9.

[0083] Comparative Example 2

[0084] Compared with Example 9, the esterification product in step A3 in Example 3 was replaced with the cyclodextrin product in step A1, and then the microcapsules s prepared according to step A3 in Example 3 replaced the antibacterial microcapsules obtained in Example 3, that is, no hindered phenol was introduced to prepare a PVDC composite film.

[0085] Comparative Example 3

[0086] Compared with Example 9, the nitro product containing carbon nanotubes obtained in step B2 of Example 6 was used to replace the thermal conductivity enhancer obtained in Example 9, that is, no epoxy group was introduced, to prepare a PVDC composite film.

[0087] The antibacterial and oxygen-barrier PVDC composite film prepared by the present invention was further tested for its effect, and the test results are described as follows.

[0088] The tensile strength and elongation at break of the composite films obtained in Examples 7-9 and Comparative Examples 1-3 were determined with reference to GB / T13022-1991 "Test Method for Tensile Properties of Plastic Films"; the antibacterial rate of the composite films was determined at room temperature for 48 hours using Escherichia coli and Staphylococcus aureus as the test bacteria, and the composite films were placed in an oven at 100°C for 48 hours, and the change rate of tensile strength after high temperature treatment was determined; the composite films were placed in an oven at an ultraviolet radiation intensity of 0.89 W / m 2 After treatment at a temperature of 50°C and an aging time of 48h, Escherichia coli and Staphylococcus aureus were used as the test bacteria, and the antibacterial rate after UV aging treatment was determined and recorded in Table 1;

[0089] Table 1:

[0090]

[0091]

[0092] According to the data in Table 1, it can be seen from the comparison between Examples 7-9 and Comparative Example 1 that the antibacterial and oxygen-barrier PVDC composite film prepared by the present invention has excellent mechanical properties, antibacterial properties, heat resistance and oxidation resistance. Comparison between Example 9 and Comparative Example 2 shows that the antioxidant properties of the antibacterial microcapsules introduced with hindered phenols are improved, which is beneficial to the improvement of the antioxidant properties of the composite film. After oxidative aging caused by ultraviolet light, the antibacterial microcapsules can maintain high antibacterial properties, thereby giving the composite film high antibacterial properties. Comparison between Example 9 and Comparative Example 3 shows that the thermal stability of the composite film is significantly improved by using carbon nanotubes introduced with epoxy groups as thermal conductivity enhancers, and the tensile strength retention rate after high-temperature treatment is still very high.

[0093] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.

Claims

1. An antibacterial and oxygen-barrier PVDC composite film, characterized in that: From the inside to the outside, it includes a PE film layer, an EVA hot melt adhesive film layer and a PVDC film layer; the PVDC film layer is obtained by coating a PVDC emulsion; the PVDC emulsion includes the following raw materials in parts by weight: 100 parts of vinylidene chloride, 10-15 parts of vinyl chloride, 60-70 parts of methyl acrylate, 5-7 parts of emulsifier, 2-4 parts of initiator, 0.5-1.5 parts of pH buffer, 80-100 parts of deionized water, 5-10 parts of antibacterial microcapsules, and 10-20 parts of thermal conductivity enhancer; The preparation of the antibacterial microcapsules comprises the following steps: Step A1: Add vinyl polydimethylsiloxane to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4-5 hours to obtain an epoxy product; add ethylenediamine cyclodextrin and the epoxy product to a round-bottom flask, then add dimethyl sulfoxide, stir and react at 50°C for 24 hours, filter, and dry to obtain a cyclodextrin product; Step A2: Add 3,5-di-tert-butyl-4-hydroxyphenylacetic acid to DMF, add dichlorothionyl under stirring, reflux and stir at 50°C for 4-5h to obtain an acyl chloride product; add cyclodextrin product, pyridine, triethylamine and dimethyl sulfoxide to a flask to obtain a mixed solution 1; add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 to the mixed solution 1 in a 0°C ice-water bath, after the dropwise addition is completed, heat to 40°C, stir at a constant temperature for 8-10h, then heat to 100-110°C, continue stirring for 1-2h, and distill under reduced pressure to obtain an esterification product; Step A3: Add the esterification product to distilled water and stir for 30 minutes to obtain solution a. Then add oregano essential oil to anhydrous ethanol to obtain solution b. Slowly add solution b to solution a while stirring. Stir and react at 50°C for 3 hours. Then place in a refrigerator at 4°C overnight. Extract with ethyl acetate and freeze-dry for 24 hours to obtain antibacterial microcapsules.

2. The antibacterial and oxygen-barrier PVDC composite film according to claim 1, characterized in that: In step A1, the usage ratio of vinyl polydimethylsiloxane, dichloromethane and 3-chloroperoxybenzoic acid is 10-12 g: 55-65 mL: 18-20 g; the usage ratio of ethylenediamine cyclodextrin, epoxy product and dimethyl sulfoxide is 12-12.5 g: 5-6 g: 35-40 mL.

3. The antibacterial and oxygen-barrier PVDC composite film according to claim 1, characterized in that: In step A2, the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, DMF, and dichlorothionyl is 0.1 mol: 55-65 mL: 0.12-0.15 mol; the usage ratio of cyclodextrin product, pyridine, triethylamine, and dimethyl sulfoxide is 14-16 g: 10-15 mL: 15-20 mL: 35-45 mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 0.1 mol: 65-75 mL; and the usage ratio of mixed solution 1 and mixed solution 2 is 90-100 mL: 85-95 mL.

4. The antibacterial and oxygen-barrier PVDC composite film according to claim 1, characterized in that: In step A3, the usage ratio of the esterification product and distilled water is 1 g:10 mL; the usage ratio of oregano essential oil and anhydrous ethanol is 1 mL:1 mL; and the usage ratio of solution b and solution a is 2.5-3 mL:12-13 mL.

5. The antibacterial and oxygen-barrier PVDC composite film according to claim 1, characterized in that: The preparation of the thermal conductivity enhancer comprises the following steps: Step B1: After ball milling the carbon nanotubes for 2-3 hours, add them to the mixed acid, start stirring, reflux at 100-120°C for 1.5-2.5 hours, dilute, filter, wash, and dry in an oven at 110°C for 6-8 hours to obtain carboxyl-modified carbon nanotubes; add the carboxyl-modified carbon nanotubes to DMF, add dichlorothionyl under stirring, reflux and react at 50°C for 4-5 hours to obtain the acyl chloride product 1; Step B2: Add p-nitrobenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution a; add the acyl chloride product 1 into dimethyl sulfoxide to obtain a mixed solution b; slowly dropwise add the mixed solution b into the mixed solution a in a 0°C ice-water bath; after the dropwise addition is completed, heat to 40°C, stir at constant temperature for 8-10h, then heat to 100-110°C, continue stirring for 1-2h, and distill under reduced pressure to obtain a nitro product; Step B3: Add the nitro product and ethyl acetate into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5 hours to obtain an aromatic primary amine; add epichlorohydrin, toluene, an aromatic primary amine and tetrabutylammonium bromide into a flask, start stirring, and condense and reflux at 110°C for 3 hours to obtain a ring-opening product, add the ring-opening product into a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain a thermal conductivity enhancer.

6. The antibacterial and oxygen-barrier PVDC composite film according to claim 5, characterized in that: In step B1, the amount ratio of carbon nanotubes and mixed acid is 10-15g:80-90mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the mass fractions of concentrated sulfuric acid and concentrated nitric acid are both 98%; the amount ratio of carboxyl-modified carbon nanotubes, DMF, and dichlorothionyl is 1.5-2.0g:30-40mL:0.12-0.15mol.

7. The antibacterial and oxygen-barrier PVDC composite film according to claim 5, characterized in that: In step B2, the dosage ratio of p-nitrobenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.01-0.015 mol: 0.1 mol: 35-45 mL; the dosage ratio of acyl chloride product 1 and dimethyl sulfoxide is 5-6 g: 30-40 mL; the dosage ratio of mixed solution a and mixed solution b is 50-60 mL: 90-100 mL.

8. The antibacterial and oxygen-barrier PVDC composite film according to claim 5, characterized in that: In step B3, the usage ratio of the nitro product, ethyl acetate and sodium dithionite is 16-18 g: 110-120 mL: 35-40 g; the usage ratio of epichlorohydrin, aromatic primary amine, toluene and tetrabutylammonium bromide is 27-30 g: 20-25 g: 120-130 mL: 0.05-0.08 mol; the usage ratio of the ring-opening product and the sodium hydroxide solution is 3-4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%.

9. The antibacterial and oxygen-barrier PVDC composite film according to claim 1, characterized in that: The PE film layer is composed of a PE film; the EVA hot melt adhesive film layer is prepared using an EVA composite adhesive; the emulsifier is a mixture of sodium dodecyl sulfate and dodecylphenol polyoxyethylene ether in a mass ratio of 2.5:1, the initiator is potassium persulfate, and the pH buffer is disodium hydrogen phosphate.

10. The method for preparing an antibacterial and oxygen-barrier PVDC composite film according to claim 1, characterized in that: The steps include: Step S1: Add vinylidene chloride, vinyl chloride, methyl acrylate, emulsifier, pH buffer and deionized water to a high-pressure reactor, stir at room temperature and a speed of 200 r / min for 15-25 minutes to obtain a pre-emulsion, then add an initiator to the deionized water, stir for 5 minutes, add to the high-pressure reactor, exhaust, start stirring, adjust the speed to 300 r / min, increase the temperature to 55-65° C., stir and react for 5 hours, heat to 65-75° C. and mature for 1 hour, start cooling to room temperature after 15 minutes, then add antibacterial microcapsules and thermal conductivity enhancers, continue stirring for 30 minutes and then discharge to obtain a PVDC emulsion; the amount ratio of deionized water before and after is 4:1; Step S2: placing a PE film to form a PE film layer, then coating the PE film with EVA composite adhesive to a thickness of 5 μm to form an EVA hot melt adhesive film layer, and finally coating the PVDC emulsion on the EVA hot melt adhesive film layer to a thickness of 15-18 μm, and then drying at 100-110° C. for 25-35 minutes to form a PVDC film layer, thereby obtaining an antibacterial and oxygen-blocking PVDC composite film.